Developing deep learning-based worksheets using google earth for elementary geography learning enhancement - Nono Tri Kartila; Jasrial Jasrial; Zelhendri Zen; Abna Hidayati (Journal of Educational and Learning Studies, 2026)
This study aimed to develop and evaluate a Deep Learning-based Student Worksheet (LKPD) integrated with Google Earth and WebMAGMA for teaching Indonesia's geographical location to fifth-grade elementary school students. A Research and Development approach employing the Four-D (4D) model Define, Design, Develop, and Disseminate was adopted. The worksheet was evaluated through expert validation, practicality testing involving teachers and students, and effectiveness testing using pre-test and post-test assessments. The worksheet demonstrated excellent validity (96.75%) and practicality (95%). Students' mean achievement increased from 53.18 to 86.82, with a high N-Gain (0.71), while learning mastery improved from 4% to 90%. The developed worksheet is valid, practical, and effective for enhancing elementary students' understanding of Indonesia's geographical location while supporting technology-enhanced implementation of the Merdeka Curriculum